2009
DOI: 10.1523/jneurosci.5715-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Toll-Like Receptor 9 Signaling as a Method for Ameliorating Alzheimer's Disease-Related Pathology

Abstract: The pathogenesis of Alzheimer's disease (AD) is thought to be related to the accumulation of amyloid ␤ (A␤) in amyloid deposits and toxic oligomeric species. Immunomodulation is emerging as an effective means of shifting the equilibrium from A␤ accumulation to clearance; however, excessive cell mediated inflammation and cerebral microhemorrhages are two forms of toxicity which can occur with this approach. Vaccination studies have so far mainly targeted the adaptive immune system. In the present study, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
164
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(167 citation statements)
references
References 45 publications
2
164
1
Order By: Relevance
“…Experimental evidence, however, found that they are inefficient in removing fibrillar A␤ (Bolmont et al, 2008), suggesting that either the deposition of A␤ itself or secondary metabolic or inflammatory events lead to a progressive impairment of microglial clearance function. Strategies to overcome this microglial paralysis are under intense investigation and include vaccination against full-length or truncated A␤ peptides or stimulation of Tolllike receptor signaling (Okura et al, 2008;Scholtzova et al, 2009). Here it is demonstrated that LXR activation is able to reset microglial function, in particular, the capacity for A␤ phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence, however, found that they are inefficient in removing fibrillar A␤ (Bolmont et al, 2008), suggesting that either the deposition of A␤ itself or secondary metabolic or inflammatory events lead to a progressive impairment of microglial clearance function. Strategies to overcome this microglial paralysis are under intense investigation and include vaccination against full-length or truncated A␤ peptides or stimulation of Tolllike receptor signaling (Okura et al, 2008;Scholtzova et al, 2009). Here it is demonstrated that LXR activation is able to reset microglial function, in particular, the capacity for A␤ phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our work supports the hypothesis that SR-BI is involved in amyloid pathology primarily as a modulator of the perivascular macrophage response. Activation of the peripheral immune cells through receptors of the innate immune system, such as the TLR9, has been shown to reduce AD-related pathology and CAA in AD mouse models (38). Similarly, SR-BI activation could possibly have a beneficial effect in AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…A␤ load in immunostained tissue sections was quantified using a BZ-Analyzer (Keyence Corp.) as reported previously. 19 Seven sections per animal were analyzed. The total A␤ burden was quantified for the hippocampus in coronal plane sections stained using the monoclonal antibody 4G8.…”
Section: Immunohistochemistrymentioning
confidence: 99%